Association of Chest Xray (CXR) findings with outcomes in COVID-19 Patients - Ainan Arshad; Ahmed Ayaz; Muhammad Abdullah Javed; Muhammad Anees; Kiran Hilal; Bushra Jamil (Journal of the Pakistan Medical Association, 2022)
Objective: To investigate chest radiography findings in suspected coronavirus disease-2019 patients in a tertiary care setting. Methods: The retrospective study was conducted at the Aga Khan University Jospital, Karachi, and comprised data of coronavirus disease-2019 cases admitted to the tertiary care centre from March 1 to March 30, 2020. A predesigned proforma was used to gather data, including demographics, like age and gender, co-morbidities, presenting symptoms and chest radiography findings during the admission. Length of stay and mortality were the outcome measures. Data was analysed using SPSS 22. Results: Of the 154 suspected cases, 46(29.8%) tested positive for coronavirus disease-2019; 29(63%) males and 17(37%) females with a mean age of 50.7±19.1 years. Abnormal chest radiography was noted in 25(54.3%) cases, with bilateral pulmonary infiltrates being the most common finding 19(41.3%). Mortality was the outcome in 7(28%) of these cases, and the mean length of hospital stay was 9.3±7.3 days. Abnormal chest radiography findings were associated with an increased risk of mortality (p=0.009) and a longer hospital stay (p=0.017). Conclusion: Abnormal chest radiography findings were frequently seen in coronavirus disease-2019 patients and were also associated with increased risk of mortality and prolonged hospital stay. Key words: Covid, X-ray, Coronavirus, Mortality.